PERANAN MEDIA PEMBELAJARAN DALAM MENGEMBANGKAN KECERDASAN INTELEKTUAL ANAK SD I MARDIATUL ISLAMIYAH DI MEDAN TEMBUNG - Daulay, Afrahul Fadhila; Nur'Aini, Nur'Aini; Siregar, Siti Rahma Dewi; Hasanah, Nur (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Learning media is anything that can be used to channel the sender's message to the recipient, so that it can stimulate students' thoughts, feelings, attention and interest in learning. This research highlights the importance of the role of learning media in developing the intellectual intelligence of children at SD I Mardiatul Islamiyah in Medan Tembung District. The method used in this research is a descriptive method with a qualitative approach. The object of this research is the 3rd grade students of SD I Mardiatul Islamiyah. The techniques used in this research are observation, interviews and documentation techniques. From the survey results, problems during teaching are where children have difficulty learning, in educating children to learn and solve problems so that children can think more, and we use learning tools to find out characteristics in children. Â Teachers must use learning media well to make classroom learning smooth and effective.